NYSTAGMUS AND BEYOND: A RARE OCULAR MOTILITY DISORDER - Naqaish, Rehan; Sadiq, Naqaish; Salam, Zauha; Arif, Abdus Salam; Parvez, Ateeb (Journal of Ayub Medical College Abbottabad, 2018)
Joubert syndrome is a rare autosomal recessive disorder predominantly involving the cerebellar vermis and brain stem. It is characterized clinically by global developmental delay, abnormal ocular movements, hypotonia, ataxia, intellectual disability and neonatal breathing abnormalities. Due to its uncommon and unconventional presentation, its diagnosis is usually delayed. Diagnosis of this atypical disease essentially relies upon the atypical finding of the molar tooth sign on Magnetic Resonance Imaging (MRI). We report a case of a 5-year-old boy who presented with abnormal eye movements, regression of milestones and developmental delay. MRI investigation revealed the distinctive molar tooth sign and bat wing shaped 4th ventricle. It requires high levels of clinical suspicion and holistic approach to such children who present with delayed milestones and abnormal eye movements, to reach at early detection and diagnosis of such rare pathologies. Keywords: autosomal recessive; molar tooth sign; Joubert syndrome